"They're Not Willing To Accommodate Deaf patients": Communication Experiences of Deaf American Sign Language Users in the Emergency Department. (January 2022) - James, Tyler G.; Coady, Kyle A.; Stacciarini, Jeanne-Marie R.; McKee, Michael M.; Phillips, David G.; Maruca, David; Cheong, JeeWon
Deaf people who use American Sign Language (ASL) are more likely to use the emergency department (ED) than their hearing English-speaking counterparts and are also at higher risk of receiving inaccessible communication. The purpose of this study is to explore the ED communication experience of Deaf patients. A descriptive qualitative study was performed by interviewing 11 Deaf people who had used the ED in the past 2 years. Applying a descriptive thematic analysis, we developed five themes: (1) requesting communication access can be stressful, frustrating, and time-consuming; (2) perspectives and experiences with Video Remote Interpreting (VRI); (3) expectations, benefits, and drawbacks of using on-site ASL interpreters; (4) written and oral communication provides insufficient information to Deaf patients; and (5) ED staff and providers lack cultural sensitivity and awareness towards Deaf patients. Findings are discussed with respect to medical and interpreting ethics to improve ED communication for Deaf patients.